Effect of casirivimab-imdevimab on mild COVID-19 patients with diabetes in reducing oxygen supplementation at 28 days: an observational study - T., Bhagyanath; R., Remitha K.; R., Akshay C.; P., Aswin; S., Deepak; R., Jithesh (International Journal of Research in Medical Sciences, 2022)
Background: Monoclonal antibody therapy is one of the most promising treatments for COVID-19 infection. Casirivimab-imdevimab is a monoclonal antibody cocktail which is approved for high-risk patients with mild to moderate COVID-19 infection. The aim of the study was to determine the safety and efficacy of casirivimab-imdevimab on diabetic patients with COVID-19. Methods: This was an observational study conducted on diabetic patients admitted with mild to moderate COVID-19 infection. The patients were divided into 2 groups. While 101 patients were administered with casirivimab-imdevimab (test group), 100 of them were provided with standard treatment (control group). Regular follow-ups ensued for 10 days during the period of their hospitalization and finally on the 28th day through a telephonic enquiry. Apart from this, safety of administering the drug was assessed in all patients who belonged to the test group. Results: One of the patients who were administered casirivimab-imdevimab developed anaphylactic reaction. Three fourth of the patients who participated in the study were vaccinated and the oxygen requirement up to 10 days of admission was significantly lower in the vaccinated group (p=0.018). Oxygen requirement, mechanical ventilation and death up to 10 days of admission were less for patients who were administered monoclonal antibody, but it was not statistically significant. Oxygen requirement, and death after 10 days up to 28 days were also less for patients who were administered monoclonal antibody, even though not statistically significant. Conclusions: Casirivimab-imdevimab was not found to be beneficial in diabetic patients with mild COVID-19. More studies with higher sample size are required to prove the clinical benefit of casirivimab-imdevimab beyond doubt.